MANAGEMENT AND FINANCIAL MANAGEMENT SYSTEM OF BOARDING SCHOOLS (Study at Pondok Pesantren La Tansa 2 Lebak-Banten) - Deni Tri Atmaja; R Melda Maesarach; Jaharuddin Jaharuddin; Dedi Zulkarnain (Media Riset Bisnis Ekonomi Sains dan Terapan, 2023)
The purpose of the study was to determine the description of pesantren financial management. This research uses a qualitative method. Financial management of boarding schools is one of the management substances of educational institutions that will help determine the smooth running of boarding school activities. As is the case with the substance of education management in general, the financial management activities of the la tansa 2 boarding school are carried out through the process of planning, directing, coordinating, supervising or controlling. Some financial management activities are in the form of activities to obtain and determine funding sources, utilization of funds, reporting, inspection and accountability. Through financial management activities, the funding needs of boarding school activities can be planned, procured, recorded transparently, and used to finance the implementation of boarding school programs effectively and efficiently. The results of the study explain that financial management is an act of financial management / administration which includes recording, planning, implementing, accountability and reporting. Thus, school financial management can be interpreted as a series of activities to manage school finances starting from planning, bookkeeping, spending, monitoring and accountability of school finances.Keywords: Management, Finance, and Pesantren